Effect of Azospirillum and VA Mycorrhiza on the Growth of Cocoa Seedlings and Incidence of Seedling Blight Disease - Sunitha Anie Cheriyan (Department of Plant Pathology, College of Horticulture, 2001)
An experiment was conducted at the College of Horticulture, Vellanikkara on the "effect of Azospirillum and V A mycorrhiza on the growth of cocoa seedlings and incidence of seedling blight disease", during 1998-2000. The experiment was conducted using native isolates and commercial cultures of Azospirillum and V A mycorrhiza. The objective of the experiment was to find out whether there is any synergistic effect for the combined inoculation of Azospirillum and V A mycorrhiza in improving the growth and establishment of cocoa seedlings and to find out the efficacy of the inoculants in imparting resistance to seedling blight disease. The first experiment showed that there was a positive influence for both V A mycorrhiza and Azospirillum in improving the growth parameters. The height and number of leaves were maximum in native Azospirillum inoculated plants. Native mycorrhizal inoculation recorded maximum height of plant while the number of leaves was maximum in plants inoculated with commercial V A mycorrhiza inoculant. Combined inoculation of native Azospirillum and V A mycorrhiza ranked only second but it was on par with the best treatment combination. The native isolates of both the inoculants and their combination was found to increase the height to the maximum. Maximum number of leaves was noted in plants inoculated with commercial V A mycorrhiza. V A mycorrhizal inoculation did not influence the number of leaves. The results on the leaf length